2017
DOI: 10.1038/sc.2017.82
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, validity and sensitivity to change of neurogenic bowel dysfunction score in patients with spinal cord injury

Abstract: The Turkish version of the NBD score is a valid and reliable instrument and also sensitive to change in patients with SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
(36 reference statements)
0
12
0
1
Order By: Relevance
“…More attention needs to be paid to the recovery of sacral autonomic function in clinical trials pertaining to neurologic recovery after SCI. However, review of relevant outcome measures [20][21][22] reveals a lack of information regarding retention of bladder sensation and control of voiding in commonly used outcome measures that focus on quality of life issues.…”
Section: Discussionmentioning
confidence: 99%
“…More attention needs to be paid to the recovery of sacral autonomic function in clinical trials pertaining to neurologic recovery after SCI. However, review of relevant outcome measures [20][21][22] reveals a lack of information regarding retention of bladder sensation and control of voiding in commonly used outcome measures that focus on quality of life issues.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who did not understand the questionnaire for the NBD score were excluded. The nature of the injury or disease was evaluated according to international standards for the neurological classification of spinal cord injury [14]. The clinical and demographic characteristics of patients are shown in Table 1.…”
Section: Methods Patientsmentioning
confidence: 99%
“…Another methodological issue is differentiation between clinical importance and statistical significant. They reported that a statistically significant negative correlation was detected between bodily pain (r = −0.3, P = 0.01), general health (r = −0.5, P < 0.001), vitality (r = −0.6, P < 0.001), social role functioning (SF) (r = −0.7, P < 0.001), emotional role functioning (r = −0.6, P < 0.001), and mental health (r = −0.6, P < 0.001) subscales, whereas no significant correlation was found with physical functioning (PF) (r = −0.2, P = 0.13) and physical role functioning (RP) (r = 0.06, P = 0.67) subscales of SF-36 [1]. In both positive and negative association, we should emphasize on the strength of the association instead of statistical significant because the second issue dramatically depends on the sample size.…”
mentioning
confidence: 93%
“…I was interested to read the paper by Erdem et al [1] published in Spinal Cord, July 2017. The purpose of the authors was to investigate the validity and reliability of neurogenic bowel dysfunction (NBD) score.…”
mentioning
confidence: 99%
See 1 more Smart Citation